The Linguistic Manifestation of Concepts: A Cognitive and Pragmatic Approach - Mirzohid qizi, Karimova Muslima (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
A concept represents a complex cognitive unit formed in human consciousness, embodying knowledge about a particular phenomenon or notion. This study examines the process of linguistic manifestation of concepts, encompassing their formation, linguistic association, contextual adaptation, and cultural implications. Using the example of the Uzbek concept of "tarbiya" (upbringing), this paper explores how concepts transition from mental representations to linguistic expressions, shaped by individual, social, and cultural contexts. The research highlights the cognitive-pragmatic mechanisms underlying this process and their significance in understanding language-cognition interactions.